Regulation in the hedge fund industry - Betsalel, Jonathan (2013)
The hedge fund industry in South Africa is currently unregulated, which is generally considered a hindrance by hedge fund managers. Some fund managers are under the impression that regulation will bring more credibility to the industry and, in turn, increase investment into this sector. The feeling is that many investors shy away from this unregulated market as there are no procedures in place to ensure that their funds will be properly managed and that, currently, investors have no recourse should the investment be mismanaged.How one applies the regulation will have profound implications. Due to their global nature, the impact of regulations with regards to both local and foreign hedge funds also needs to be addressed. The implication of regulating the industry needs to be addressed from all aspects, including, for example, cost and industry agility.Although the South African government has been threatening to regulate the industry since 2001, it has yet to do so. Recently, there has been renewed hope that the government will introduce regulations to the industry; however, some fund managers are skeptical. === Dissertation (MBA)--University of Pretoria, 2010. === Gordon Institute of Business Science (GIBS) === unrestricted